In vitro suppression of interleukin 2 production by Mycobacterium leprae antigen - Makonkawkeyoon S. (2014)
The suppressive activity of three different lots and sources of Mycobacterium leprae (M. leprae) was studied by measuring the inhibitory effect on interleukin 2 (IL-2) production in normal subjects. All three M. leprae preparations had suppressive activity on IL-2 production when peripheral blood mononuclear leucocytes (PBML) were stimulated with the mitogens PHA-P or Con A in a dose response. M. leprae also had suppressive activity on IL-2 production when PBML were stimulated with the specific antigen, PPD. The inhibitory activity of M. leprae on IL-2 was not due to the direct interaction of M. leprae and IL-2 because direct mixing of IL-2 with different concentrations of M. leprae did not alter the activity of IL-2. Incorporation of M. leprae for 0, 6 and 12 h in PHA-P and PBML cultures had no inhibitory effect on IL-2 production; however, after 14, 16 and 18 h of M. leprae incorporation, significant inhibitory effects were noted on IL-2 production. The suppressive mechanism of M. leprae was studied by incorporating M. leprae into PBML or adherent cells. The suppressive activity could be detected in both M. leprae-stimulated PBML and M. leprae-stimulated monocyte supernatant fluids. The suppressive mechanism of M. leprae was further evaluated by incorporating 1 and 2 micrograms/ml of indomethacin in PBML containing PHA-P and M. leprae. The suppressive activity of M. leprae was significantly diminished by indomethacin, suggesting that the inhibitory effect of M. leprae may result from the induction of PBML and adherent cells to produce the immunosuppressive activity of prostaglandin(s).